PEMANFAATAN MEDIA DADU BERGAMBAR DALAM PEMBELAJARAN MENULIS KARANGAN TEKS DESKRIPSI PADA SISWA KELAS IV SDN MLATIHARJO 2 - Nabila Khoirunnisa; Lintang Kusumawardani; Umi Virgianti; Rani Setiawaty (Universitas Muhammadiyah Kuningan, 2024)
The use of pictorial dice media is an innovative approach in learning to write descriptive text essays. This research aims to provide a description of the benefits of pictorial dice media in learning to write descriptive text essays for class IV students at SDN Mlatiharjo 2. This research uses a qualitative descriptive research type with research subjects namely class IV teachers and class IV students at SDN Mlatiharjo 2, while the object is dice. pictorial. Data collection techniques in this research used observation, interview and documentation techniques. Data analysis techniques use data reduction, data presentation, and drawing conclusions. Data validity techniques use source triangulation to obtain different evidence through interviews, observations and documentation. Based on this research, the results show that using picture dice has benefits in writing descriptions, namely that it can develop new ideas, increase student creativity, help enrich student vocabulary, and help students understand the structure of writing descriptive text. Therefore, the use of pictorial dice media can be used as an effective strategy in students' learning to write descriptive text essays.